2016
DOI: 10.1063/1.4972133
|View full text |Cite
|
Sign up to set email alerts
|

Double-layer buffer template to grow commensurate epitaxial BaBiO3 thin films

Abstract: We propose a BaCeO3/BaZrO3 double-layer buffer template, grown on a SrTiO3 substrate, for epitaxial growth of a target oxide film with large lattice constants of over 4.1 Å. Lattice mismatch from the substrate was mostly accommodated for by a BaZrO3 arbitrating layer. Having an ideal in-plane lattice structure, BaCeO3 served as the main-buffer to grow the target material. We demonstrated commensurate epitaxy of BaBiO3 (BBO, a = 4.371 Å) utilizing the new buffer template. Our results can be applied to heteroepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In contrast to the studies on the synthesis of BBO single crystals, reports on epitaxial growth of BBO thin films are limited. It has been shown that, aside from the growth on MgO substrates (lattice mismatch of ≈1.4%), smooth and well‐ordered BBO thin films can be deposited on SrTiO 3 substrates (lattice mismatch of ≈12%) through domain matching epitaxy even without the use of buffer layers such as BaO and BaCeO 3 /BaZrO 3 . BBO films can be further used as buffer layers for the stabilization of the energetically unfavorable, but electronically nontrivial perovskite phase in the YBiO system .…”
mentioning
confidence: 99%
“…In contrast to the studies on the synthesis of BBO single crystals, reports on epitaxial growth of BBO thin films are limited. It has been shown that, aside from the growth on MgO substrates (lattice mismatch of ≈1.4%), smooth and well‐ordered BBO thin films can be deposited on SrTiO 3 substrates (lattice mismatch of ≈12%) through domain matching epitaxy even without the use of buffer layers such as BaO and BaCeO 3 /BaZrO 3 . BBO films can be further used as buffer layers for the stabilization of the energetically unfavorable, but electronically nontrivial perovskite phase in the YBiO system .…”
mentioning
confidence: 99%
“…To realize the energetically unfavourable perovskite phase, the use of a buffer layer is investigated. In literature buffer layers are often used to con-trol the in-plane strain [13,14], quality [15,16] and crystal orientation [17] of the film deposited on top. BaBiO 3 (BBO) is suggested as suitable buffer layer material, since it has a lattice constant (a=4.35 Å [18]) comparable to the predicted perovskite YBO and it is stable in the perovskite phase.…”
mentioning
confidence: 99%
“…K). A number of reports on the growth of undoped or hole-doped BBO films by molecular beam epitaxy (MBE) and pulsed laser deposition have recently appeared [9,10,16,[24][25][26][27][28][29]. One challenge is to find perovskite substrates to match BBOs large pseudocubic lattice parameter ∼4.35 Å. SBO has a smaller pseudocubic lattice parameter ∼4.25 Å resulting in a reasonable lattice match to some large lattice-parameter perovskite substrates such as BaSnO 3 (∼4.12 Å) and LaLuO 3 (∼4.18 Å).…”
mentioning
confidence: 99%